Field emission studies of novel ZnO nanostructures in high and low field regions - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S.; Pillai, Vijayamohanan K. (Nanotechnology, 2006)
A study of the field emission characteristics of novel structures of ZnO, namely marigolds, multipods and microbelts, has been carried out in both the close proximity configuration and the conventional field emission microscope. The use of a conventional field emission microscope overcomes the drawback of arc formation at high field values. The nonlinearity in the Fowler - Nordheim ( F - N) plot, a characteristic feature of semiconductors has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability exhibited by these structures is also promising for future device applications.

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Field emission investigation of single Fe-doped SnO2 wire - Bhise, Ashok B.; Late, Dattatray J.; Sathe, Bhaskar R.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Solid State Sciences, 2009)
Tin oxide submicronwires doped with Fe element were prepared by the thermal evaporation method. Morphological and structural characterizations revealed wires with sub micron size and crystalline in nature. The field electron emission from the single Fe:SnO2 wire was carried out in conventional field emission microscope. The Fowler-Nordheim plot obtained from I-V characteristics of the wire showed a linear behavior typical that of metal. The field enhancement factor estimated from the slope of the F-N plot is 7455 cm(-1), indicating that the field emission is from nanometric features of the emitter. A current density of 10 A/cm(2) has been obtained at an applied field of 4.845 x 10(3) V/mu m. The field emission current-time record at a current level of 1 mu A for more than 3 h duration is promising for various field emissions based applications. (C) 2009 Published by Elsevier Masson SAS.
Keywords: Current stability; Fe doped; field emission; SnO2

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

Facile synthesis of Ag nanowire-rGO composites and their promising field emission performance - Samantara, Aneeya K.; Mishra, Dillip Kumar; Suryawanshi, Sachin R.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Jena, Bikash Kumar; Rout, Chandra Sekhar (RSC Advances, 2015)
Crystalline, ultra long silver nanowires (Ag NWs), few-layered rGO (reduced graphene oxide) and their rGO-Ag NW nanocomposite have been synthesized using a polyol reflux technique under optimized experimental conditions. The field emission performance of the rGO-Ag NW nanocomposite, rGO and Ag NW emitters was investigated. The turn on field required to draw an emission current density of similar to 1 mA cm(-2) was found to be similar to 5.00, 3.92 and 2.40 V mu m(-1) for the Ag NW, rGO and rGO-Ag NW nanocomposite emitters, respectively. The combined contribution of the sharp edges of the thin graphene sheets and high aspect ratio of the Ag nanowires, and their synergetic effect in the rGO-Ag NW nanocomposite, are responsible for the enhanced field emission behavior. First-principles density functional calculations show that the enhanced field emission may also be due to the overlapping of the electronic structures of the Ag NWs and rGO nanosheets.

Field emission properties of spinel ZnCo2O4 microflowers - Ratha, Satyajit; Khare, Ruchita T.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2015)
ZnCo2O4 microflowers were synthesized by a simple low temperature hydrothermal route. A single three-dimensional microflower consists of hundreds of self-assembled petals, with a thickness of several nanometers. These microflowers have exceptionally thin edges with a few petal layers. The ZnCo2O4 microflowers appeared to be stable and good field emitters.

Facile approach towards fabrication of GdB6-ZnO heteroarchitecture as high currentdensity cold cathode - Suryawanshi, Sachin R.; Mistari, Chetan D.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Chemistryselect, 2016)
Three dimensional (3D) GdB6-ZnO heteroarchitecture comprised of thin coating of GdB6 on self aligned ZnO urchins with pointed apex has been synthesized employing optimized Pulsed Laser Deposition (PLD) technique. The self aligned ZnO urchins on Zn substrate were obtained using hydrothermal route. The as-synthesized GdB6-ZnO heteroarchitecture was characterized using XRD, SEM, TEM XPS, and UPS in order to reveal its structural, morphological, chemical, and electronic properties. Interestingly, the GdB6-ZnO heteroarchitecture exhibits superior field emission (FE) behviour in contrast to the pristine ZnO urchins envisaged by extraction of very high emission current density of similar to 4.6 mA/cm(2) at an applied field of similar to 4.5 V/mm, against similar to 1.5 mA/cm(2) at an applied field of similar to 5.6 V/mm from the pristine ZnO urchins emitter. Furthermore, the GdB6-ZnOemitter exhibits good emission stability at pre-set value of similar to 5 mA over duration of more than 3 hours. The superior FE behaviour of the GdB6-ZnO is attributed to low work-function of GdB6 and presence of nanometric protrusions on the emitter surface, further enhancing the aspect ratio provided by the ZnO urchins. The present results demonstrate a facile approach towards fabrication of high current density cold cathodes due to rare earth hexaborides via designing hetero-architectures comprised of their well adherent ultrathin coating on high aspect ratio metal oxide nanostructures.

Field emission properties of highly ordered low-aspect ratio carbon nanocup arrays - Gupta, Bipin Kumar; Kedawat, Garima; Kumar, Pawan; Singh, Satbir; Suryawanshi, Sachin R.; Agrawal, Neetu; Gupta, Govind; Kim, Ah Ra; Gupta, R. K.; More, Mahendra A.; Late, Dattatray J.; Hahm, Myung Gwan (RSC Advances, 2016)
Herein, we design and develop a field emission device utilizing highly porous carbon nanocup (CNC) films. These three-dimensional (3D) low-aspect ratio CNC structures were fabricated by a combination of anodization and chemical vapor deposition techniques. The low turn-on fields of 2.30 V mu m(-1) were observed to draw an emission current density of 1 mu A cm(-2) and a maximum emission current density of similar to 1.802 mA cm(-2) drawn at an applied field of similar to 4.20 V mu m(-1). The enhanced field emission behavior observed from the CNC films is attributed to an excellent field enhancement factor of 1645. The observed field emission properties of CNC arrays are attributed to a synergistic combination of high aspect ratio, nano-sized radius of curvature, highly organized distribution of the emitters over the whole area of specimen and lower screening effect of the CNC arrays. These observations shed light on the effect of the stacking carbon layers of CNC on their electronic properties and open up possibilities to integrate new morphologies of graphitic carbon in nanotechnology applications. Thus, the low turn on field, high emission current density and better emission current stability enable CNC based future field emission applications.

Facile process for ammonia sensing using electrospun polyvinylidene fluoride/polyaniline (PVDF/PANI) nanofibers chemiresister - Kondawar, Sanchit; Late, Dattatray J.; Anwane, Rajashree S.; Kondawar, Subhash B.; Koinkar, Pankaj; Parinov, Ivan A. (Advanced Materials, 2019)
Electrospun polyvinylidene fluoride/polyaniline (PVDF/PANI) nanofibers chemiresister was fabricated by electrospinning and polymerization. As-fabricated PVDF/PANI nanofibers chemiresister was characterized by SEM, FTIR, TGA and DTG analyses. Cost effective with high accuracy microcontroller based sensor set up was designed for the measurement of change in resistance of chemiresister with respect to different concentrations of ammonia gas at various temperatures. The semiconducting behavior of the chemiresister was found to respond quickly towards ammonia gas. High sensitivity, fast response and recovery of PVDF/PANI nanofibers for ammonia gas at room temperature confirmed the chemiresister as potential candidate for ammonia sensing in environmental monitoring safety systems, chemical and automotive industries.

Facile production of mesoporous WO3-rGO hybrids for high-performance supercapacitor electrodes: an experimental and computational study - Samal, Rutuparna; Chakraborty, Brahmananda; Saxena, Manav; Late, Dattatray J.; Rout, Chandra Sekhar (ACS Sustainable Chemistry & Engineering, 2019)
This work explored a promising supercapacitor electrode material (WO3-rGO hybrids) synthesized via a simplistic one-pot hydrothermal synthesis route. Various analytical studies (X-ray diffraction study, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis) were employed in furtherance to explore the structural, morphological, compositional, and surface areal properties of the prepared materials. The enhancement in electrochemical supercapacitive properties were evaluated from pure hexagonal phase WO3 to the various hybrids, depending on the concentration of GO introduced into it, using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy. The WG-80 composite revealed the high rise in capacitance value of 801.6 F/g overcoming the individual capacitance of rGO (71.11 F/g) and WO3 (94.22 F/g) at a current density of 4 A/g with good cycling stability (75.7%) over 5000 cycles. We have presented quantum capacitance from ab initio calculations and provided theoretical explanation from the orbital interactions.
Keywords: Density functional theory; Hydrothermal method; supercapacitor; WO3-rGO hybrids

Fundamentals and sensing applications of 2D materials - Hywel, Morgan; Rout, Chandra Sekhar; Late, Dattatray J. (Elsevier, 2019)
Fundamentals and Sensing Applications of 2D Materials provides a comprehensive understanding of a wide range of 2D materials. Examples of fundamental topics include: defect and vacancy engineering, doping and advantages of 2D materials for sensing, 2D materials and composites for sensing, and 2D materials in biosystems. A wide range of applications are addressed, such as gas sensors based on 2D materials, electrochemical glucose sensors, biosensors (enzymatic and non-enzymatic), and printed, stretchable, wearable and flexible biosensors. Due to their sub-nanometer thickness, 2D materials have a high packing density, thus making them suitable for the fabrication of thin film based sensor devices.

Future prospects of 2D materials for sensing applications - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
Two-dimensional (2D) material attracted significant research interest from the discovery of graphene in 2004. These 2D materials allow a platform for artificial integration of heterostructures with unique platforms that show exotic physical attributes and phenomenon as well as properties and applications. Each layer in 2D materials consist of a covalent bond, a dangling bond-free lattice, and weak van der Waals (vdWs) interaction. This makes it feasible to fabricate lateral and vertical vdWs heterostructures without the constraints of lattice matching and processing compatibility. These vdWs heterostructures open a door for a broad range of applications in electronics, optoelectronics, flexible devices, sensors, and photovoltaics. In this chapter, we have critically assessed the recent developments in 2D materials, the fabrication of heterostructures, and their application for sensing purposes. We conclude with current challenges and ideas concerning future developments in this merging field.